2009
DOI: 10.1161/circulationaha.108.783340
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Aneurysm of the Main Pulmonary Artery

Abstract: Since the first introduction of pulmonary balloon valvuloplasty by Kan in 1982, the procedure has been used for relief of pulmonary valve stenosis. It is normally recommended that the procedure should be performed for peak-topeak gradients in excess of 50 mm Hg, 1 and the balloon/ annulus ratio should be 1.2 to 1.25 for effective and safe results. 2 Complications of the procedure are minimal and rare. We present the case of dissecting aneurysm of the main pulmonary artery, a dangerous complication of pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A variety of mechanisms have been proposed to explain the discrepant phenotypes in VSMC upon activation of Notch signaling. For example, it is well documented that endothelial expression of Jag-1 is required for activation of Notch3 on VSMC and maintenance of VSMC maturation and contraction (High et al, 2008; Liu et al, 2009), while others have shown a variety of mechanisms by which active Notch signaling inhibits VSMC differentiation and the contractile phenotype (Havrda et al, 2006; Li et al, 2009a). Work from our laboratory supports the former finding in that activation of Notch receptors in human primary VSMC using immobilized Jag-1 promotes upregulation of contractile proteins (Boucher et al, 2011; Figure 3A).…”
Section: Molecular Mechanisms Of Notch Signaling In Vsmcmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of mechanisms have been proposed to explain the discrepant phenotypes in VSMC upon activation of Notch signaling. For example, it is well documented that endothelial expression of Jag-1 is required for activation of Notch3 on VSMC and maintenance of VSMC maturation and contraction (High et al, 2008; Liu et al, 2009), while others have shown a variety of mechanisms by which active Notch signaling inhibits VSMC differentiation and the contractile phenotype (Havrda et al, 2006; Li et al, 2009a). Work from our laboratory supports the former finding in that activation of Notch receptors in human primary VSMC using immobilized Jag-1 promotes upregulation of contractile proteins (Boucher et al, 2011; Figure 3A).…”
Section: Molecular Mechanisms Of Notch Signaling In Vsmcmentioning
confidence: 99%
“…Support for the involvement of Notch in mediating VSMC proliferation and neointimal formation comes from a study in which carotid artery ligations were used to induce the formation of a neointima in mice harboring one of the following genotypes: a general heterozygous deletion of Notch1 (Notch1 +/− ), a VSMC specific heterozygous deletion of Notch1 (VSMC–Notch1 +/− ), or a homozygous general deletion of Notch3 (Notch3 −/− ; Li et al, 2009a). In this report, researchers show negligible differences in neointimal formation between wild type and Notch3 −/− , while Notch1 +/− and VSMC–Notch1 +/− resulted in post-carotid ligation decrease in neointimal lesion formation by 70%.…”
Section: Notch Signaling Mediates Vsmc Proliferation and Neointimal Lmentioning
confidence: 99%
“…Treatment of pulmonary artery dissection is surgical in case of symptomatic patients [14]. Nonoperative treatment is reserved for stable asymptomatic patients [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary artery dissection is suspected in the face of sudden hemodynamic decomposition in an otherwise previously stable patient with known presentation of pulmonary hypertension or pulmonary artery aneurysm [13]. The condition progresses rapidly, so prompt diagnosis permits surgical treatment, which improves prognosis [14, 15]. Fortunately, several imaging modalities, such as chest radiograph, echocardiography, CT angiography, MRI, and cardiac catheterization, have been available for the evaluation of pulmonary artery dissection.…”
Section: Discussionmentioning
confidence: 99%
“…There is no definite guideline as the optimal treatment for pulmonary artery dissection. Surgical intervention may be necessary for most patients but it is usually followed by fatal consequences [12, 14]. Unfortunately, this patient suddenly died before surgical intervention.…”
Section: Discussionmentioning
confidence: 99%